English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Mathematics

2006-09-18 10:40:27 · 4 answers · asked by Greyci G 1 in Science & Mathematics Mathematics

4 answers

in point slope form, which is generally:

m(x-x1)=y-y1

plugging in:

-3(x+2) = y+1

in slope intercept form,
-3x-6=y+1
y=-3x-7

2006-09-18 10:42:25 · answer #1 · answered by need help! 3 · 0 0

It is very easy. The equation may have the form y-y1=m(x- x1) where m is the slope and (x1,y1) the point. You have just to put the number there: y +1 = -3(x+2) and you have the equation. You may change the form to y = -3x -3 if you want, but it is not necessary.

2006-09-18 10:45:09 · answer #2 · answered by vahucel 6 · 0 0

y+1=-3(x+2)
y+1=-3x-6
3x+y+7=0

2006-09-18 10:44:19 · answer #3 · answered by raj 7 · 0 0

ur just another lazy kid wanting to get answers without working to find an answer

2006-09-18 10:49:01 · answer #4 · answered by JJcD 4 · 0 0

fedest.com, questions and answers